The irruption of science in medical ethics: neuroethics and Freud´s psychoanalysis - Figueroa Cave, Gustavo (Acta Bioethica, 2016)
Psychoanalysis and neuroethics are concerned with ethical issues arising in the application of techniques and technologies stemming from the sciences of the mind. There is considerable overlap between the topics covered in neuroethics and in conceptual issues with which psychoanalists have long been concerned. Relying on a biologistic perspective, whereby only what is biological is real, neuroehtics offers a vision of ethics that limits the significance of the unique psychoanalytic concern: the understanding of unconscious meanings and the role of discourse in discerning and justifying these meanings. Neurethics has been leading ethics toward an appreciation of the sensory, the physical, the visual, at the expense of psychological meaning, the psychic dimension of human existence.